Dual Response Optimization of Ultrasound-Assisted Oil Extraction from Milkfish By-Products using D-Limonene as A Bio-Based Solvent - Masrukan, Masrukan; Raharjo, Sri; Yanti, Rini; Setyaningsih, Widiastuti (Trends in Sciences, 2024)
Fish oil has been reported to have positive health effects because it is rich in n-3 essential fatty acids. This study aimed to determine the optimal conditions for achieving a high oil yield and omega-3 content from milkfish by-products using ultrasound-assisted extraction (UAE) combined with a d-limonene solvent. The Box-Behnken design (BBD) combined with response surface methodology was successfully used to determine the optimum extraction conditions for omega-3 fatty acids based on several factors: Temperature (30, 60 and 90 °C), solvent-to-sample ratio (2:1, 4:1 and 6:1 mL/g) and time (6, 38 and 70 min). The ANOVA results showed that sonication time (p < 0.05) and temperature (p < 0.05) had a significant influence on omega-3 fatty acids and the yield of extracted oil. The optimal extraction conditions for UAE were 68 min, 84 °C, and a solvent-to-sample ratio of 3:1 mL/g resulting in high oil recovery (21.95 %) containing omega-3 compounds (12.50 %). Additionally, the resulting oil was also further characterized by quality parameters (acid, peroxide, anisidine-total oxidation and iodine values) as well as the fatty acid composition. The developed milkfish oil met the IFOS™ (International Fish Oil Standards) criteria hence applicable for industrial oil production. HIGHLIGHTS Milkfish is extensively utilized to produce fillets, resulting in a variety of by-products. Milkfish by-products can be converted into fish oil, which is a source of omega-3 that benefits health. Ultrasound-assisted extraction (UAE) expedites fish oil extraction by shortening processing time. The optimal UAE conditions were 68 min, 84 °C, and solvent-to-sample ratio of 3:1 mL/g. D-limonene combined with UAE extracted fish oil rich in omega-3 (12.5 %) from milkfish by-products. GRAPHICAL ABSTRACT